2017
DOI: 10.5539/elt.v10n3p111
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Communication Skills among Engineering Students

Abstract: Good communication skills are of utmost importance in the education of engineering students. It is necessary to promote not only their education, but also to prepare them for the demanding and competitive job market. The purpose of this study was to compare the attitudes towards communication skills after formal instruction between the students of engineering studies in the first and sixth semesters. Data were collected using the Communication Skills Attitude Scale (CSAS) which consisted of 14 items. The targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…One participant (P5) suggested conflict management as an interpersonal skill without mentioning the construct directly. This finding supports the study by Kovac and Sirkovic (2017), who justified that the skill to resolve conflict was desirable in a workplace in order to become a productive team member. According to Mehrabian (2008), 7% of individual communication is verbal communication that contains content and meaning, 38% is non-verbal communication, such as voice, intonation, and tone, while 55% of communication contains body language communication.…”
Section: Interpersonal Communicationsupporting
confidence: 89%
“…One participant (P5) suggested conflict management as an interpersonal skill without mentioning the construct directly. This finding supports the study by Kovac and Sirkovic (2017), who justified that the skill to resolve conflict was desirable in a workplace in order to become a productive team member. According to Mehrabian (2008), 7% of individual communication is verbal communication that contains content and meaning, 38% is non-verbal communication, such as voice, intonation, and tone, while 55% of communication contains body language communication.…”
Section: Interpersonal Communicationsupporting
confidence: 89%
“…Although the majority of students clearly described a positive attitude about being recorded, a few students had a negative attitude toward recording the presentations, which is in line with the studies of Kovac and Sirkovic (2017) and Ihmeideh et al (2010). Unlike Murphy and Barry (2016), who found some reasons why a small number of students disagreed with the utility of the self-reflection exercise 4 we have no reason to explain why a few respondents reported a negative attitude.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, it is not easy for them to study communication skills by reading; they must be taught these skills using more varied multisensory techniques before they reach the graduate level or enter the labor market. Previous work has confirmed that senior students have higher positive and lower negative attitudes toward communication skills than students at the beginning of their undergraduate studies (Ihmeideh, Al-Omari, & Al-Dababneh, 2010;Kovac & Sirkovic, 2017). This paper responds to a call from the existing literature: that it is of great importance for students to have more opportunities to develop communication skills at the beginning of their university education (Kovac & Sirkovic, 2017).…”
Section: Introductionmentioning
confidence: 54%
“…Communication skills are strongly tied to students' academic and future professional success [16]. Developing communication skills has always been one of the greatest concerns of most teachers and students in any field of study and especially in second language education (17)(18)(19). In the context of the 21st century, communication is deemed as one of the four essential skills that students are expected to develop.…”
Section: Literature Reviewmentioning
confidence: 99%